2015
DOI: 10.1007/s00426-015-0697-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation and the subjective feeling of “aha!” are independently related to learning from insight

Abstract: It has been proposed that sudden insight into the solutions of problems can enhance long-term memory for those solutions. However, the nature of insight has been operationalized differently across studies. Here, we examined two main aspects of insight problem-solving—the generation of a solution and the subjective “aha!” experience—and experimentally evaluated their respective relationships to long-term memory formation (encoding). Our results suggest that generation (generated solution vs. presented solution)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
88
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 54 publications
3
88
1
1
Order By: Relevance
“…is better than for problems encoded without Aha! (Danek et al, 2013a;Dominowski & Buyer, 2000;Kizilirmak et al, 2015). Such an Aha!…”
Section: The Aha! Experience and Later Memorymentioning
confidence: 99%
See 4 more Smart Citations
“…is better than for problems encoded without Aha! (Danek et al, 2013a;Dominowski & Buyer, 2000;Kizilirmak et al, 2015). Such an Aha!…”
Section: The Aha! Experience and Later Memorymentioning
confidence: 99%
“…experience was phrased such that generation was not a necessary precondition; the solution could still be comprehended suddenly, appearing utterly convincing and clear as day when it was comprehended after it was presented following a failed attempt at problem solving. Using this procedure, Kizilirmak et al (2015) found that the Aha! experience was accompanied by a more positive feeling and better memory performance independent of whether the solution to a problem was generated or not.…”
Section: The Aha! Experience and Later Memorymentioning
confidence: 99%
See 3 more Smart Citations